2011
DOI: 10.1530/jme-10-0165
|View full text |Cite
|
Sign up to set email alerts
|

CD82 gene suppression in endometrial stromal cells leads to increase of the cell invasiveness in the endometriotic milieu

Abstract: Tetraspanin CD82 is a wide-spectrum tumor metastasis suppressor that inhibits motility and invasiveness of cancer cells. Endometriosis is a benign gynecological disorder, but appears malignant behaviors including invasion, ectopic implantation and recurrence. This study is to elucidate the role of CD82 expression regulation in the pathogenesis of endometriosis. The short interfering RNA silence was established to analyze the roles of CD82, chemokine CCL2, and its receptor CCR2 in the invasiveness of endometria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…1F, right), and invasion ( Fig. 1G) (P< .01), which echoes our previous results (8). In addition, the proliferation, viability, and invasiveness of normal ESCs are lower than that of the eutopic ESCs.…”
Section: Ccl2 Promotes the Viability Proliferation And Invasivenesssupporting
confidence: 89%
See 1 more Smart Citation
“…1F, right), and invasion ( Fig. 1G) (P< .01), which echoes our previous results (8). In addition, the proliferation, viability, and invasiveness of normal ESCs are lower than that of the eutopic ESCs.…”
Section: Ccl2 Promotes the Viability Proliferation And Invasivenesssupporting
confidence: 89%
“…Recent research has established that the up-regulation of survival-relative molecules and invasion-relative molecules may cooperatively contribute to survival and invasion of endometriosis, such as matrix metalloproteinases (MMPs) (8,9), survivin (9), proliferating cell nuclear antigen (PCNA), and cyclooxygenase (COX)-2 (10). Several investigators reported a relationship between CCL2 levels in serum (11,12) or peritoneal fluid (PF) (12,13) and endometriosis.…”
mentioning
confidence: 99%
“…Thus, aberrantly high levels of CD82 in the decidua may block the invasion of trophoblasts, resulting in early pregnancy termination. Also, CD82 mRNA and protein levels become lower in the ESCs from a eutopic endometrium and ectopic endometriotic tissue in patients with endometriosis [102].…”
Section: Female Reproductive Systemmentioning
confidence: 96%
“…CD82 silencing in ESCs promotes the invasiveness of firsttrimester trophoblasts by increasing CCL2 secretion, CCR2 expression, integrin β1 levels, and MAPK signaling and by decreasing TIMP1 expression [101,102]. The reduced invasiveness of trophoblasts probably results from the increased release of TIMP1 by CD82-expressing, decidualized ESCs [101].…”
Section: Female Reproductive Systemmentioning
confidence: 99%
See 1 more Smart Citation